1998
DOI: 10.1103/physrevb.58.9763
|View full text |Cite
|
Sign up to set email alerts
|

Semimetallic behavior inFe2VAl:NMR evidence

Abstract: We report the results of a 27 Al and 51 V nuclear magnetic resonance study of Fe 2 VAl at temperatures between 4 and 550 K. This material has been a subject of current interest due to indications of possible heavy fermion behavior. The low-temperature NMR relaxation rate follows a Korringa law, indicating a small density of carriers at the Fermi level. At elevated temperatures, the shifts and relaxation rates go over to a thermally activated response, a semiconductorlike behavior, consistent with separate low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
81
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 19 publications
9
81
4
Order By: Relevance
“…Therefore, in Ref. 5 it has been speculated that the (magneto)resistivity of Fe 2 VAl reflects a mixture of electron excitation processes over the pseudogap and spin dependent scattering from impurities.Independently, on basis of specific heat and NMR-experiments it has been demonstrated that in Fe 2 VAl crystallographic disorder, assumed to be present in form of atomic site exchange between Fe and V atoms, substantially affects the ground state properties of this compound [10,11]. In particular, the anomalous low temperature specific heat has been attributed to ferromagnetic clusters with a density of 0.003-0.004/unit cell, consistent with the results from NMR experiments.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Therefore, in Ref. 5 it has been speculated that the (magneto)resistivity of Fe 2 VAl reflects a mixture of electron excitation processes over the pseudogap and spin dependent scattering from impurities.Independently, on basis of specific heat and NMR-experiments it has been demonstrated that in Fe 2 VAl crystallographic disorder, assumed to be present in form of atomic site exchange between Fe and V atoms, substantially affects the ground state properties of this compound [10,11]. In particular, the anomalous low temperature specific heat has been attributed to ferromagnetic clusters with a density of 0.003-0.004/unit cell, consistent with the results from NMR experiments.…”
supporting
confidence: 74%
“…From our Mössbauer data we can estimate for sc-Fe 2 VAl the required number of site exchanged Fe II/V pairs: to account for the broadening of the Mössbauer-line below T C it would require at least 6% Fe II on V sites. This value, which is more than one order of magnitude larger than the estimated level of Fe/V site exchanges for q-Fe 2 VAl of 0.3-0.4% [10,11], is inconsistent with the result of our neutron diffraction experiments, setting an upper limit of 3% Fe II on V sites. Therefore, we conclude that neither model proposed so far properly accounts for the Mössbauer spectra of Fe 2+x V 1−x Al, x≈0.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…The actual g(E F ) should be somewhat larger. Okamura et al 3 using photoconductivity measurements also reported similar results for Fe 2 VAl with a band gap of 0.1-0.2 eV and a finite DOS at the Fermi level. The experimental results of the band gap and the temperature range in which they were measured are summarized in Table I.…”
supporting
confidence: 61%
“…These experimental results were quite intriguing. This dual nature was also seen in NMR experiments by Lue et al 2 By measuring the T -dependence of Knight shift (K s ) and the nuclear spin relaxation time (T 1 ) and fitting these two quantities to functions of E g /T , they found a band gap of 0.21-0.22 eV for K s and 0.27 eV for T 1 . Surprisingly, in addition to the activated behaviour, they also found metallic characteristics through Korringa law.…”
mentioning
confidence: 75%